2010
DOI: 10.1111/j.1750-3841.2010.01629.x
|View full text |Cite
|
Sign up to set email alerts
|

α‐Glucosidase Inhibitory Activity of Bromophenol Purified from the Red Alga Polyopes lancifolia

Abstract: A bromophenol, bis(2,3-dibromo-4,5-dihydroxybenzyl) ether, was purified from the red alga Polyopes lancifolia. Its IC(50) values were 0.098 and 0.120 microM against Saccharomyces cerevisiae and Bacillus stearothermophilus alpha-glucosidases, respectively, and 1.00 and 1.20 mM against rat-intestinal sucrase and maltase. This bromophenol competitively inhibited S. cerevisiae alpha-glucosidase with a K(I) value of 0.068 microM and was very stable at pH 2 for 60 min at 37 degrees C. Therefore, this P. lancifolia b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 34 publications
1
61
1
2
Order By: Relevance
“…Therefore, many researchers are looking for more potent compounds with anti-inflammatory characteristics. Polyopes lancifolius, mainly found in the Republic of Korea and Japan, is such a seaweed with medicinal value [11]. Only one study has been conducted and this revealed that bromophenol purified from P. lancifolia, which was thought to be the same species as P. lancifolius, may have potential as a natural nutraceutical for treating type 2 diabetes [11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many researchers are looking for more potent compounds with anti-inflammatory characteristics. Polyopes lancifolius, mainly found in the Republic of Korea and Japan, is such a seaweed with medicinal value [11]. Only one study has been conducted and this revealed that bromophenol purified from P. lancifolia, which was thought to be the same species as P. lancifolius, may have potential as a natural nutraceutical for treating type 2 diabetes [11].…”
Section: Introductionmentioning
confidence: 99%
“…Seaweed extracts are rich in phytochemicals such as polyphenols, phlorotannins, and phloroglucinol derivatives that have been shown to exhibit antidiabetic activity through inhibition of α-amylase and α-glucosidase activity (Lee et al 2009;Kim et al 2010). Besides inhibition of the carbohydrate-hydrolyzing enzymes, another important antidiabetic mechanism previously postulated is via antioxidant activity (Wang et al 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Marine algae produce a wide range of new secondary metabolites with various biological activities which may have potential applicability in the field of pharmaceutical industry to provide a stable platform for medicine industries [15]. Several bioactive compounds from red algae such as Rhodomela confervoides, Symphyocladia latiuscula, Polysiphonia urceolata and brown marine algae have been experimentally tested for their biomedical efficacy [16][17][18].…”
Section: Methodsmentioning
confidence: 99%